Experimental Study on Machining Engineering Ceramics by Electrochemical Discharge Compound Grinding - Xu, Kun (Materials (Basel), 2019)
Since engineering ceramics have many characteristics, including hardness, brittleness, and high melting point, traditional machining methods can no longer play a useful role in precision machining. Based on this situation, a platform of electrochemical discharge compound mechanical grinding was constructed and is presented in this paper, and machining experiments of micro-grooves were carried out in alumina ceramics. Grooves were observed by scanning electron microscope (SEM), and the morphology and the groove width of micro-grooves under different machining parameters were compared and analyzed. Furthermore, in order to study the improvement effect of mechanical grinding on machining quality, the surface roughness of micro-grooves was measured by a confocal material microscope. The results show that as the pulse power supply voltage increases or the frequency decreases, the width of the micro-grooves increases, and the morphology of the micro-grooves first improves and then deteriorates. With the increase of tool electrode rotation speed, the width of micro-grooves first increases and then remains unchanged, and the morphology and the surface roughness of micro-grooves first improves and then remains stable. Finally, the optimal parameters (power voltage of 20 V, pulse frequency of 400 Hz, electrode rotation speed of 600 rpm) were chosen to machine micro-grooves with good quality.